Reducing the Diameters of Computer Networks - Bokhari, S. H.; Raza, A. D. (IEEE transactions on computers, 1986)
We discuss three methods of reducing the diameters of computer networks by adding additional processor to processor links under the constraint that no more than one I/O port be added to each processor. This is equivalent to adding edges to a given graph under the constraint that the degree of any node be increased, at most, by one.